Presentation: Creating emotional awareness through drama in the second language acquisition - Galazka, Alicja (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2016)
Drama as a teaching medium seems to be a solution for working with students not only on linguistic progress but also on developing their emotional potential. It helps to develop students’ emotional and social competences which are extremely important in second language acquisition. This article focuses on using drama as a medium of working with children in a bilingual nursery in Poland. It describes the project based on the action research taken in Poland.